ASSESSING POPULATION GENETIC STRUCTURING OF SOUTHERN AFRICAN MARINE ORGANISMS IN THE FACE OF AN UNCERTAIN CLIMATIC FUTURE - (:unkn) unknown (My University, 2010)
South Africa is the meeting point of two great and dynamic oceanic currents, with the associated coastline comprising highly variable bioregions that affect the distribution and abundance of marine species. In order to understand the patterns of population structure and gene flow along 3500 kms of South African coastline, species with large geographical ranges and differing life history characteristics (i.e. broadcast spawning, brooding and live bearing) were sequenced for mtDNA and nuclear genes. Organisms included molluscs, crustaceans, echinoderms and fishes (16 spp), this paper particularly focussing on the latter. For almost all species, results suggest that the last glacial maximum (~22,000 yrs ago) had a major influence on the evolutionary history, as well as population genetic patterns of these organisms. Most populations have remained stable for the past 5000 years. However, several physical and biological indicators suggest a warming trends in the southern African oceans, such as the warming of the Agulhas Current. Southern Africa has a west-east coast conformation, which provides little opportunity for population refugia, especially for organisms endemic to the south coast. This talk evaluates some possible scenarios relating to genetic diversity, population genetic structuring and gene flow patterns in a warming ocean, especially with reference to upwelling and other oceanographic events that are highly important in creating barriers to gene flow. Understanding the historical, contemporary and future processes influencing population structuring will influence not only the management practices of exploited marine species, but will contribute to the management and conservation of the entire southern African coast.
Keywords: African Research